Agglutination-Inhibition Assay for the Detection of Recombinant Proteins Tagged with Peptide Epitopes. (May 1997) - Dolezal, Olan; Coia, Gregory; Hudson, Peter J.
We have demonstrated that the expression of recombinant proteins labeled with an immunoreactive epitope can be rapidly assessed and quantitated using a modified haemagglutination inhibition assay in enzyme-linked immunosorbent assay (ELISA) trays. The agglutination of erythrocytes from a droplet of whole blood provided a simple visual assay. The additional reagents required for the assay were a recombinant anti-human erythrocyte Fab fragment fused to a peptide epitope and a bivalent antibody with specificity to the same epitope. In this report, we found that a convenient and sensitive epitope was the octapeptide FLAG ® in conjunction with the M2 anti-FLAG antibody, which had affinity to FLAG incorporated either at the C-terminus or N-terminus of the recombinant protein. The agglutination-inhibition (AI) assay was configured to detect as little as 1 mg/L of soluble recombinant protein in a 30-min assay. Since the AI assay was substantially more rapid and convenient than dot-blot or Western blot analyses, our laboratory now uses this method routinely for the assay of FLAG-labeled recombinant products following protein expression and subsequent small- and large-scale purification procedures.